The Effects of Carbonate on Candida albicans Filamentation, Biofilm Formation, and Antifungal Resistance - Trenton P. Miedema; Kayla E. Grooters; Ian A. Cleary (MicrobiologyOpen)
ABSTRACT Candida albicans, a member of the normal microbial population of healthy humans, is an opportunistic pathogen that can cause serious disease in immunocompromised patients. An important virulence factor of C. albicans is the formation of biofilms. These organized communities of cells are efficient at attaching to host cells and implanted medical devices. Carbonate has been studied as an agricultural antifungal agent, and here we demonstrate that carbonate can affect filamentation, biofilm formation, and antifungal drug resistance in C. albicans.